PHOTO-DEGRADATION OF SURFACTANT COMPOUNDS USING UV RAYS WITH ADDITION OF TIO2 CATALYSTS IN LAUNDRY WASTE - Hendra, Hendra; Barlian, Eri; Razak, Abdul; Sanjaya, Hary (IAIN Batusangkar, 2015)
The utility of synthetic cleaners or commonly called as detergents have developed far indeed in this century. The effective and efficient use of detergents in cleaning process, was attracted to be used in laundry?s industry commercially, though, it has some drawback to the society and environments. Since the active materials in the compounds can cause irritating to the skins, cataracts to mature eyes and some other environmental issues due to the excess of foams can prevent oxygen dilution in the water so it be hazardous to water living organisms. Once the promising method to solve this problem is by photo-degradation using photo-catalyst. Photo-catalyst is the process using light and catalyst in order to accelerate chemical transformation, thus, solar or uv-rays can be used as light sources. This research aims at to show the ability of catalyst TiO2 to degrade active material in linear alkyl benzene sulphonate (LAS) and alkyl benzene sulphonate (ABS) which is available in commercial detergent. Photo-degradation of LAS and ABS compounds was determined by optimum capacity TiO2 and irradiance time. Whereas, for environmental application, the degrade compounds such Rinso® and Wipol® was chosen since it is commonly used in daily life. Beside, artificial water waste and laundry water was chosen to show the environmental effect. The result shows that the optimum number of catalyst TiO2 addition for LAS degradation was 1.5 g, and optimum time was 120 minute. Whereas the optimum number of catalyst TiO2 addition for ABS degradation was 2.0 g, and optimum time was 120 minute as well. Thus, for detergent Rinso®, at optimum catalyst addition, we found degradation number was 75.83%, and for detergent Wipol®, at optimum catalyst addition, we found degradation number was 57.94%. Whereas, for artificial waste at optimum catalyst addition, we found degradation number was 91.32%, and for laundry water waste at optimum catalyst addition, we found degradation number was 70.27%.Key words : Photodegradation, surfactant, TiO2, photocatalyst